Iceland, UK and Brexit : How can Iceland and the UK make a better trade deal in lieu of Brexit? - Viktor Daðason 1993- (2018)
When Brexit has been fully implemented, the UK will need to renegotiate its trade deals with non-EU countries such as Iceland. The aim of the thesis will be to discover the scenario that will lead to an optimal trade deal for both countries involved. The UK and Iceland will aim for a conclusive and mutually beneficial trade agreement between both countries. In the optimal solution, both countries will have a free trade of goods and materials, with the exception of agricultural goods plus fish and seafood. Both products will have a similar trade tariff between Iceland and the United Kingdom. In order to support this case, the thesis will cover some trade history on Iceland, the UK, EU and EFTA, how Brexit came to exist, the methodology that will used, trade numbers, possible protectionist measures between both countries, the pros and cons of international trading, the intricacies of trade deal negotiations alongside with Peterson institute for international economics guide on trade negotiations.